Code-switching as appraisal resource in talking about third parties - Baumgarten, Nicole; Du Bois, Inke (Linguistik Online, 2012)
This article explores the function of code-switching in talking about absent third parties. The basis for the investigation is a corpus of sociolinguistic individual and group interviews with German immigrants in the US and American immigrants in Germany. In these interviews, the interviewees are asked to recount their migration experiences and their lives before and after migration. For each individual speaker, the interviewer and – in the group interviews – the other participants in the group are, on the one hand, potentially 'sympathetic' fellow migrants. On the other hand, however, they are potentially problematic figures, because talking about absent third parties means that these third parties might share characteristics with the interviewer or the others in the group. Talking about third parties can, thus, be face-threatening for both the interviewer and the interviewees. In the analyses presented in this article, we identify how speakers employ English-to-German code-switching when it comes to verbalizing others – specifically members of home and host cultures – in discourse and how they position themselves and their audience in relation to them.